2008
DOI: 10.1002/poc.1437
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ versus intermolecular hydrogen bonding equilibrium in 2‐hydroxy‐N,N‐diethylbenzamide

Abstract: Complex studies of the intramolecular versus intermolecular hydrogen bond equilibrium and internal rotation of the N,N‐diethylamine group in 2‐hydroxy‐N,N‐diethylbenzamide were conducted. The intramolecular versus intermolecular process in 2‐hydroxy‐N,N‐diethylbenzamide was studied by UV–Vis, NMR, IR and Vapour Pressure Osmometric (VPO) methods as a function of temperature and concentration in non‐polar, basic and protic solvents. The unequal positions of the ethyl groups were analysed and the energy barrier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…One of the ways to overcome this problem is to reduce the sample temperatures to slow down the molecular motions, for example by using Freon as a solvent that freeze below 100 K, although usually the solubility of organic molecules in such solvents is low . On the other hand, NMR at room and evaluated temperatures can be successfully applied to study intramolecular or sterically protected H‐bonds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways to overcome this problem is to reduce the sample temperatures to slow down the molecular motions, for example by using Freon as a solvent that freeze below 100 K, although usually the solubility of organic molecules in such solvents is low . On the other hand, NMR at room and evaluated temperatures can be successfully applied to study intramolecular or sterically protected H‐bonds …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] On the other hand, NMR at room and evaluated temperatures can be successfully applied to study intramolecular or sterically protected H-bonds. [1,[6][7][8] Hydrogen bonds formed by amides play an important role in biological systems. For example, such H-bonds hold together the secondary structure of proteins and the structure of deoxyribonucleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a detailed description of the conformation of systems with the amide moiety is very important. In the papers [66][67][68][69], it was shown that salicylamides can form two types of hydrogen bonds-intramolecular in 5-chloro-2-hydroxy-benzamide and intermolecular in 2-hydroxy-N,N-diethylbenzamide in the solid state ( Figure 14). Studies of the IR, NMR (Nuclear Magnetic Resonance), and UV-Vis spectra, recorded as a function of temperature in non-polar, proton-accepting, and proton-donating solvents [68,69], prove the existence of an equilibrium between intramolecular and intermolecular hydrogen bonds.…”
Section: Equilibrium Between Intramolecular and Intermolecular Hydrogmentioning
confidence: 99%
“…In the papers [66][67][68][69], it was shown that salicylamides can form two types of hydrogen bonds-intramolecular in 5-chloro-2-hydroxy-benzamide and intermolecular in 2-hydroxy-N,N-diethylbenzamide in the solid state ( Figure 14). Studies of the IR, NMR (Nuclear Magnetic Resonance), and UV-Vis spectra, recorded as a function of temperature in non-polar, proton-accepting, and proton-donating solvents [68,69], prove the existence of an equilibrium between intramolecular and intermolecular hydrogen bonds. It is noteworthy that the ease of breaking the strong intramolecular hydrogen bond (e.g., for 4-chloro-2-hydroxybenzamide d(O … O) = 2.526 Å) in 2-hydroxy-N,N-diethylbenzamide is the result of a strong steric effect of ethyl groups and weakened π-electronic coupling between the phenyl and amide fragments [67].…”
Section: Equilibrium Between Intramolecular and Intermolecular Hydrogmentioning
confidence: 99%
See 1 more Smart Citation